Effect of 5 months aerobic exercise with low to moderate intensity on serum liver enzymes in subclinical hypothyroidism women - Mohammad Fathizadeh; Vahid Valipour Dehnou; Mohammad Fathi (Mashhad University of Medical Sciences, 2020)
Introduction: Physical activity has a beneficial effect on liver enzymes concentration. Also, patients with subclinical hypothyroidism have high levels of liver enzymes. Therefore, this study was performed with aim to investigate the effect of 5 months aerobics exercise with low to moderate intensity on serum levels of liver enzymes in subclinical hypothyroidism women. Methods: This semi-experimental study with pre-test and post-test design was performed on 25 subclinical hypothyroidism women in Abdanan city in 2016. The subjects were divided into three groups: drug-exercise, exercise, and drug. Aerobics exercise training consisted of 3 sessions (60 min) per week for 5 months. The drug group was inactive persons who took only LT4 tablets. Levels of ALT, AST and ALP were measured in three groups after 5 months. Data were analyzed using SPSS software (version 24) and correlated t-test and one-way ANOVA test. PResults: Aerobics exercise with low to moderate intensity resulted in non-significant changes in serum levels of ALT (p=0.054), AST (p=0.065) and ALP (p=0.108) in subclinical hypothyroidism women. Conclusion:According to the findings of the present study, 5 months aerobics exercise with low to moderate intensity leads to non-significant changes in serum liver enzymes of ALT, AST, and ALP in subclinical hypothyroidism women. Thus, 5 months aerobics exercise does not affect the improvement of non-alcoholic fatty liver in subclinical hypothyroidism women.